2021
DOI: 10.1111/grow.12559
|View full text |Cite
|
Sign up to set email alerts
|

The impact of knowledge base on technological innovation of emerging industries from the perspective of related variety: A case study of China’s fuel cell industry

Abstract: The location of emerging industries has been hotly debated in the field of economic geography. While the concept of Windows of Locational Opportunity proposes that new industries emerge with relative freedom in space, the literature on Regional Branching has been underlining the importance of existing knowledge base. The concept of related variety provides us with a new way to handle this ongoing debate. By dividing technological knowledge base of a region into related and unrelated knowledge bases, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For example, Neffke first systematically studied the diversity evolution path of regional 'industrial space' by analyzing the characteristics of the Swedish economic evolution from 1969 to 2002, where he found that the evolution process of this industry was significantly affected by path dependence, i.e., that new technologies or industries came from the reorganization of local related technology and industries [19]. Similar evidence can also be found in different countries or regions, such as the United States [20], Europe [21], and China [22][23][24].…”
Section: Territorial Knowledge Dynamics Schoolmentioning
confidence: 92%
“…For example, Neffke first systematically studied the diversity evolution path of regional 'industrial space' by analyzing the characteristics of the Swedish economic evolution from 1969 to 2002, where he found that the evolution process of this industry was significantly affected by path dependence, i.e., that new technologies or industries came from the reorganization of local related technology and industries [19]. Similar evidence can also be found in different countries or regions, such as the United States [20], Europe [21], and China [22][23][24].…”
Section: Territorial Knowledge Dynamics Schoolmentioning
confidence: 92%
“…Previous researches have mostly interpreted this issue from the perspectives of knowledge base, absorptive capacity, technological complexity, technical proximity and so on. For example, relevant research shows that the local knowledge base can help the region occupy the core position in the innovation network, and enable the region to better benefit from technological exchange (Mi et al., 2022). Absorptive capacity is essential for the use of knowledge in the network.…”
Section: Innovation Effect Of Technology Transfer: a Literature Reviewmentioning
confidence: 99%
“…Special absorptive capacity mainly reflects the absorptive capacity of special technologies. Knowledge base is considered as an important support for absorbing technology (Mi et al., 2022). Therefore, we use “number of patents except low‐carbon technology” to further express the absorptive capacity.…”
Section: Index Selection and Model Settingmentioning
confidence: 99%
“…Broekel and Boschma ( 2011 ) verified that cognitive proximity should be moderate, and too close cognition would hinder innovation performance. Mi et al ( 2021 ) also empirically prove that the importance of related knowledge and unrelated knowledge to innovation can be changed, thus indirectly proving the paradox of cognitive proximity. With the continuous outbreak of COVID-19 across the globe in 2020, more thoughts have been aroused on virtual collaborative research under distanced conditions (Asante et al, 2021 ).…”
Section: Introductionmentioning
confidence: 97%